Civil protection of noise: Comparative research - األستاذ المساعد الدكتور أزاد شكور صالح; المدرس المساعد يونس عثمان علي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
Noise is one of the most important elements of air pollution, as it has a harmful impact on human health, which is the mainstay of the national income of the state. It is therefore not surprising that noise pollution (auditory pollution) is called the disease of the epoch ,because the phenomenon of noise pollution has become the problem of the present era in all parts of the world, especially after industrial and technological industrialization. This phenomenon has increased both individually and collectively Recent scientific studies have proved that this phenomenon is disturbing to tranquility, and is quiet, and affects negatively on the human body, nervous system, and mood, and lead to fatigue and disorder. On the other hand, this issue raises a number of problems from the legal point of view, the most important of which concerns or interferes with harms of the unfamiliar neighborhood, including those falling within the scope of tort liability. In many cases, the rules of civil liability are incapable of Noise pollution damage,However, legislators have struggled to find solutions that ensure that the injured person gets the right compensation,And the need to develop rules relating to corporate responsibility because it is not possible to determine who is responsible,As well as those that fall within the contractual responsibility,Including those that are part of the public authorities' task of achieving public tranquility. This may be due to the multiplicity of special and public laws dealing with protection, prevention and punishment and the reduction of this phenomenon ,So we put an end to this phenomenon ,And to demonstrate to the legislator the extent of Gaps, Disadvantages. shortcomings in the texts that dealt with this phenomenon, and to develop appropriate solutions to them.